Development of innovative pothole repair materials using induction heating technology - Obaidi, Hadel Ibraheem Ahmad (2018)
Millions are spent by authorities to maintain and repair the world’s potholes. In addition to the direct costs, they can also lead to damaged vehicles and an accelerated deterioration of the road system. The potholes create traffic risks that lead to the daily loss of hundreds of work hours for drivers and passengers. Many road crews are not familiar with the proper materials and methods for pothole repair. Correct selection of pothole patching materials and proper application of repair procedures can greatly increase the longevity of pothole repairs, lead to fewer driver frustrations, and lower road maintenance budgets. The present study aims to develop innovative materials to repair of potholes by using induction heating technology.